PENGALAMAN KELUARGA MENYERTAI PASIEN SELAMA PROSES AKHIR KEHIDUPAN DI IGD RUMAH SAKIT PEMERINTAH DI JAWA BARAT - Andi Miftahul Khair; Etika Emaliyawati; Tuti Pahria (Jurnal Keperawatan Indonesia Timur (East Indonesian Nursing Journal), 2021)
Family members who take the patient to ED have high expectation but sometimes what happens if lose their beloved one. ED busy situations, small room with many patients, and lack of time to communicate with the medical team during the EOL process. When patients are in the EOL phase, the necessary treatment focuses at improving patients' life quality in order to welcome the death as they wish, die with dignity. This research applies qualitative design with a phenomenology approach. It involves participants who are 7 of nuclear family members who accompany patients during the EOL process in ED. Data were collected using an in-depth interview, analyzed using Colaizzy method. Five themes are obtained from this research namely dilemma in making a decision to stop life support, fear of being left by beloved one, guiding beloved one to pray in their final seconds, Life and Death in Allah’s Control, and dissatisfaction towards the service. This research provides a description of how the family feels after accompanying the patient during the EOL process in ED through the themes and sub-themes in this research. There is a new phenomenon emerging in this research which is not found in other research. It is the feeling of being neglected and discriminated when it comes to medical cost and BPJS insurance, and feeling of gratitude and pride of the family members who can accompany the patient till this patient die with khusnul khotimah or peacefull.